DEVELOPING AN EQUILIBRIUM OF PROTECTION OF THE RIGHT TO PRIVACY AND NATIONAL SECURITY IN TERRORISM ERADICATION IN INDONESIA - Djafar, Wahyudi; Syauqillah, Muhamad (Journal of Terrorism Studies, 2022)
Tension between privacy and security is nothing new, however due to the development of information and communication technology use as well as more intensive efforts of terrorism eradication have affected to the increasing level of the conflict. The need for national security is often similar to the situation of state of emergency, which enables the state to conduct several limitations to the implementation of right to privacy. Many states use the said justification and further position the element of national security to be in the superior position compared to the protection of civil liberties, including right to privacy. As a result, the act of limitation to the implementation of right to privacy in the context of terrorism eradication is deemed as ordinary and justified by law. In addition to that, to legitimize such policy, the state often sustains the state of emergency situation with no clear time limit. Departing from such situation, there needs to build an equilibrium between security and protection of the right to privacy by adapting to the continually changing reality. Today's technology development enables the state to track the movement of each person and create detailed and comprehensive profile of its citizen's life, so that the limitation of privacy also changes. However, even with the reason of terrorism eradication, the actions executed by the state must refer to several specific principles to ensure the protection of rights and fundamental freedoms.